The anaplastic lymphoma kinase testing conundrum. (February 2014) - Conde, Esther; Taniere, Philippe; Lopez-Rios, Fernando
<x xml:space="preserve">Abstract</x> Given the excellent results of the clinical trials with anaplastic lymphoma kinase (ALK) inhibitors, the importance of accurately identifying ALK-positive lung carcinoma patients has never been greater. It brings with it a pressing need for harmonized development of companion diagnostics, for economic, scientific and medical reasons. Therefore, it is crucial that ALK testing assays become more standardized both in performance (analytical phase) and interpretation (post-analytical phase). We find that both methods currently recommended by College of American Pathologists/International Association for the Study of Lung Cancer/Association for Molecular Pathology guidelines (FISH and Immunohistochemistry) are reasonable approaches for primary routine ALK testing, if at least 50 tumor cells are scored and protocols are strictly followed. Moreover, due to the high demand to study multiple predictive biomarkers on different assay platforms, quick and reliable approaches to achieve this are essential to guide treatment decisions.